Research progress on non-coding RNA regulatory networks and targeted therapy in diabetic nephropathy - Wang, Xiaxia; Jing, Ruge; Yang, Tong; Shao, Ruiwen; Yang, Fan; Shi, Yangyang; Yang, Xiujuan; An, Dong; Liang, Yonglin (Frontiers in Endocrinology, 2025)
Diabetic Nephropathy (DN), a leading cause of disability and mortality in patients with diabetes, has become a complex global clinical issue that poses a severe challenge to public health. Research indicates that Non-coding RNAs (ncRNAs) participate in cell death and fibrosis through an endogenous competitive RNA (ceRNA) network. This network regulates kidney-specific cells such as podocytes, mesangial cells, and renal tubular epithelial cells, thereby establishing a multifaceted regulatory mechanism in DN progression. Furthermore, exosomal ncRNAs and their ceRNA networks, stem cell-derived exosomal ncRNAs, related biomolecules, and the targeted regulation of ncRNAs and ceRNA networks by traditional Chinese medicine all play significant roles in the advancement of DN. This review systematically summarizes the content of ncRNAs, ceRNA networks and DN, exosome ncRNA intervention in DN progression, and targeted regulation of ncRNA intervention in DN progression. Concurrently, it discusses the research progress and therapeutic status of ncRNAs as clinical biomarkers, challenges facing ncRNA-targeted therapy, therapeutic efficacy of exosomal ncRNAs and stem cell-derived exosomal ncRNAs, pharmacokinetic limitations of Chinese medicine components in regulating DN progression through ncRNA intervention, and analyses the bottlenecks in ncRNA-based diagnosis and cross-species conservation of circRNAs/lncRNAs. This study aimed to provide new insights for the in-depth exploration of the molecular mechanisms underlying DN and the development of targeted therapeutic strategies.